Undersea city - Pohl, Frederik (Dobson, 1968)
A young Sub-Sea Academy cadet is assigned to the Krakatoa Dome, an experimental station three miles below the ocean, where he attempts to solve the mystery of artificial earthquakes and the disappearance of his famous scientist uncle.